Measuring inter-ethnic accomodation: are communicator style constructs adequate? - Ibrahim, Faisal; Ahmad, Abd Mua'ti @ Zamri; Tamam, Ezhar; Bolong, Jusang (SEGi University College, 2009)
This paper attempts to analyse the possibility of measuring interethnic accommodation strategies between the Malaysian Chinese and Malays using Norton’s communicator-style constructs. Focus is directed towards the communicative habits and cultural perspectives of both ethnic groups, the basic tenets of the Communication Accommodation Theory and the constructs of communicator styles. With the colour of ethnic history in the country and the assumptions of the theory there are reasons to believe that accommodation strategies adopted by the Malaysian Chinese and Malays are driven by the chronicles of history and cultural perspectives. Although the communicator style constructs are generally used to measure styles at individual level and accommodation strategies have been measured in various ways, this paper found that there is a strong reason to explore the use of the constructs to measure interethnic accommodation strategies.